Golden Berry-Derived 4β-hydroxywithanolide E for Selectively Killing Oral Cancer Cells by Generating ROS, DNA Damage, and Apoptotic Pathways - Chiu, Chien-Chih; Haung, Jo-Wen; Chang, Fang-Rong; Huang, Kuang-Jing; Huang, Hsuan-Min; Huang, Hurng-Wern; Chou, Chon-Kit; Wu, Yang-Chang; Chang, Hsueh-Wei (PLOS ONE, 2013)
Background Most chemotherapeutic drugs for killing cancer cells are highly cytotoxic in normal cells, which limits their clinical applications. Therefore, a continuing challenge is identifying a drug that is hypersensitive to cancer cells but has minimal deleterious effects on healthy cells. The aims of this study were to evaluate the potential of 4β-hydroxywithanolide (4βHWE) for selectively killing cancer cells and to elucidate its related mechanisms. Methodology and Principal Findings Changes in survival, oxidative stress, DNA damage, and apoptosis signaling were compared between 4βHWE-treated oral cancer (Ca9-22) and normal fibroblast (HGF-1) cells. At 24 h and 48 h, the numbers of Ca9-22 cells were substantially decreased, but the numbers of HGF-1 cells were only slightly decreased. Additionally, the IC50 values for 4βHWE in the Ca9-22 cells were 3.6 and 1.9 µg/ml at 24 and 48 h, respectively. Time-dependent abnormal increases in ROS and dose-responsive mitochondrial depolarization can be exploited by using 4βHWE in chemotherapies for selectively killing cancer cells. Dose-dependent DNA damage measured by comet-nuclear extract assay and flow cytometry-based γ-H2AX/propidium iodide (PI) analysis showed relatively severer damage in the Ca9-22 cells. At both low and high concentrations, 4βHWE preferably perturbed the cell cycle in Ca9-22 cells by increasing the subG1 population and arrest of G1 or G2/M. Selective induction of apoptosis in Ca9-22 cells was further confirmed by Annexin V/PI assay, by preferential expression of phosphorylated ataxia-telangiectasia- and Rad3-related protein (p-ATR), and by cleavage of caspase 9, caspase 3, and poly ADP-ribose polymerase (PARP). Conclusions/Significance Together, the findings of this study, particularly the improved understanding of the selective killing mechanisms of 4βHWE, can be used to improve efficiency in killing oral cancer cells during chemoprevention and therapy.